Morphological and molecular characterization of Hysterothylacium spp. parasitizing Pomatomus saltatrix and Pagrus pagrus of the State of São Paulo, Brazil - Serrano, Thaissa D. [UNESP]; Vieira, Diego H. M. D. [UNESP]; Pelegrini, Larissa S.; Fragoso, Lúcia V. [UNESP]; Agostinho, Beatriz N. [UNESP]; Vera, Manuel; Porto-Foresti, Fábio [UNESP]; De Azevedo, Rodney K.; Abdallah, Vanessa D. (FapUNIFESP (SciELO), 2023)
Raphidascarid nematodes have been the focus of several studies, mainly due to the zoonotic potential of some species, even though the cases are underreported. Due to the difficulty in identifying their larvae, the use of diagnostic techniques involving morphological and molecular analyses has grown in the last 20 years. The present study had as objective the morphological and molecular characterization of the L3 larval types of Hysterothylacium collected in Pomatomus saltatrix and Pagrus pagrus from the Brazilian coast, close to the municipality of Santos, State of São Paulo. Twenty specimens of P. saltatrix were necropsied and Hysterothylacium type V (n = 257) and Hysterothylacium type X (n = 5) larvae were found. Five specimens of P. pagrus were necropsied and all were parasitized by Hysterothylacium type V larvae. The analyses showed a genetic proximity relationship between Hysterothylacium types V with other Hysterothylacium V and with H. deardorffoverstreetorum, although this is a species inquirenda. Haplotypes for Hysterothylacium type X found in the present study formed a monophyletic group with other Hysterothylacium X, H. amoyense, and H. zhoushanense. Through this study, new hosts and localities were registered for Hysterothylacium type V and Hysterothylacium type X.
Keywords: ITS; Nematoda; phylogeny; Raphidascaridae; taxonomy